2001
DOI: 10.1074/jbc.m104953200
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Sensitivity of Tristetraprolin-deficient Cells to p38 Inhibitors Suggests the Involvement of Tristetraprolin in the p38 Signaling Pathway

Abstract: Treatment of macrophages with pyridinyl imidazole inhibitors of p38 protein kinases can inhibit lipopolysaccharide-stimulated tumor necrosis factor ␣ secretion. However, bone marrow-derived macrophages from tristetraprolin (TTP)-deficient mice were less sensitive than normal macrophages to this effect of p38 inhibitors, despite evidence for normal p38 activation in response to lipopolysaccharide. TTP is known to cause decreased stability of tumor necrosis factor ␣ and granulocyte-macrophage colony-stimulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
187
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(198 citation statements)
references
References 40 publications
(56 reference statements)
10
187
1
Order By: Relevance
“…In this study, the stimulation of stress-activated protein kinases induced the formation of a RNP complex that bound to a region containing the TBE and triggered stabilization of VEGF mRNA. Furthermore, it was reported that phosphorylation of TIS11 (TTP) by p38 kinase could reduce its binding affinity for ARE motifs (Carballo et al, 2001). One could then extrapolate that p38 activation might disrupt the TIS11b-TBE complex and allow recruitment of a stabilizing ARE-binding protein which remains to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the stimulation of stress-activated protein kinases induced the formation of a RNP complex that bound to a region containing the TBE and triggered stabilization of VEGF mRNA. Furthermore, it was reported that phosphorylation of TIS11 (TTP) by p38 kinase could reduce its binding affinity for ARE motifs (Carballo et al, 2001). One could then extrapolate that p38 activation might disrupt the TIS11b-TBE complex and allow recruitment of a stabilizing ARE-binding protein which remains to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2, CSF2 and IL-2 genes are dysregulated in the absence of TTP (Carballo et al, 2000;Ogilvie et al, 2005;Phillips et al, 2004), and it seems likely that expression of other inflammatory mediators will also prove to be controlled by TTP. Inflammatory mRNAs can be stabilized via the phosphorylation and inactivation of TTP by MAPK-activated protein kinase 2, a kinase that is activated by p38 MAPK (Carballo et al, 2001;Chrestensen et al, 2004;Stoecklin et al, 2004). At least in cells of the myeloid lineage, this appears to be the principal mechanism for post-transcriptional regulation of inflammatory genes by the p38 MAPK pathway.…”
Section: Tristetraprolinmentioning
confidence: 99%
“…TTP exists in numerous phosphorylated forms, which suggests that it may be targeted by several signaling pathways. TTP is phosphorylated by the mitogen-activated protein kinase (MAPK) p42, the p38 MAPK, and MAPK-activated protein kinase 2 (Taylor et al, 1995;Carballo et al, 2001;Mahtani et al, 2001). TTP binds to 14-3-3 proteins, the binding being largely dependent upon a specific site in the TTP C terminus, and the interaction between TTP and 14-3-3 proteins is biologically significant in determining cytoplasmic localization.…”
Section: Tristetraprolinmentioning
confidence: 99%